Histone deacetylase 1 controls CD4+ T cell trafficking in autoinflammatory diseases. Issue 119 (May 2021) - Hamminger, Patricia; Marchetti, Luca; Preglej, Teresa; Platzer, René; Zhu, Ci; Kamnev, Anton; Rica, Ramona; Stolz, Valentina; Sandner, Lisa; Alteneder, Marlis; Kaba, Elisa; Waltenberger, Darina; et al.
Abstract: CD4 + T cell trafficking is a fundamental property of adaptive immunity. In this study, we uncover a novel role for histone deacetylase 1 (HDAC1) in controlling effector CD4 + T cell migration, thereby providing mechanistic insight into why a T cell-specific deletion of HDAC1 protects against experimental autoimmune encephalomyelitis (EAE). HDAC1-deficient CD4 + T cells downregulated genes associated with leukocyte extravasation. In vitro, HDAC1-deficient CD4 + T cells displayed aberrant morphology and migration on surfaces coated with integrin LFA-1 ligand ICAM-1 and showed an impaired ability to arrest on and to migrate across a monolayer of primary mouse brain microvascular endothelial cells under physiological flow. Moreover, HDAC1 deficiency reduced homing of CD4 + T cells into the intestinal epithelium and lamina propria preventing weight-loss, crypt damage and intestinal inflammation in adoptive CD4 + T cell transfer colitis. This correlated with reduced expression levels of LFA-1 integrin chains CD11a and CD18 as well as of selectin ligands CD43, CD44 and CD162 on transferred circulating HDAC1-deficient CD4 + T cells. Our data reveal that HDAC1 controls T cell-mediated autoimmunity via the regulation of CD4 + T cell trafficking into the CNS and intestinal tissues. Graphical abstract: Image 1 Highlights: HDAC1 regulates CD4 + T cell adhesion to brain endothelial cells. Defects in CD4 + T cell migration underlie EAE protection of HDAC1 cKO mice. HDAC1 regulates homing of CD4 + T cells to intestinal tissues. CD4 + T cell-mediated induction of intestinal inflammation is controlled by HDAC1. HDAC1 controls CD4 + T cell-mediated autoimmunity via regulating T cell trafficking.